If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 2 + 5x = 24 Reorder the terms: 2 + -7x + 5x = 24 Combine like terms: -7x + 5x = -2x 2 + -2x = 24 Solving 2 + -2x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -2x = 24 + -2 Combine like terms: 2 + -2 = 0 0 + -2x = 24 + -2 -2x = 24 + -2 Combine like terms: 24 + -2 = 22 -2x = 22 Divide each side by '-2'. x = -11 Simplifying x = -11
| f(x)=4x(cos(5x)) | | 8n+5=4n-11 | | p=5x-4y+3z | | 2Y+X+21=0 | | y/5=-5.5 | | 12x-6=3(3x+4) | | a(n)=7+(n-1)3 | | -10h-6=-2over-5 | | -36+8x=2(2+8x) | | 4u+16=7u+1 | | 35y^2-2y+2= | | x^2+15x^2= | | 3b^2+12b+12=0 | | 9+21y= | | 21y+10=28 | | 35=4x+15 | | 150+(3x-15)=180 | | 4n-6=8 | | X+2Y+21=0 | | 8+2=30 | | 4y=y+33 | | 0=x^2+6x+17 | | -4(8x+43)-18x=4x-13(2-18) | | 2(y+2)=12 | | 0=2x^2-16x+38 | | 36=.5(x*2x) | | 44=2(3w+w) | | x^3-5x^2+3x-5x-6= | | 9+x=93 | | 2.4=x+3.7 | | 4(d+6)= | | 890/2 |